Chloroquine Increases Glucose Uptake via Enhancing GLUT4 Translocation and Fusion with the Plasma Membrane in L6 Cells - Qi Zhou; Xinzhou Yang; Mingrui Xiong; Xiaolan Xu; Li Zhen; Weiwei Chen; Yan Wang; Jinhua Shen; Ping Zhao; Qing-Hua Liu (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Chloroquine can induce an increase in the cellular uptake of glucose; however, the underlying mechanism is unclear. Methods: In this study, translocation of GLUT4 and intracellular Ca2+ changes were simultaneously observed by confocal microscope in L6 cells stably over-expressing IRAP-mOrange. The GLUT4 fusion with the plasma membrane (PM) was traced using HA-GLUT4-GFP. Glucose uptake was measured using a cell-based glucose uptake assay. GLUT4 protein was detected by Western blotting and mRNA level was detected by RT-PCR. Results: We found that chloroquine induced significant increases in glucose uptake, glucose transporter GLUT4 translocation to the plasma membrane (GTPM), GLUT4 fusion with the PM, and intracellular Ca2+ in L6 muscle cells. Chloroquine-induced increases of GTPM and intracellular Ca2+ were inhibited by Gallein (Gβγ inhibitor) and U73122 (PLC inhibitor). However, 2-APB (IP3R blocker) only blocked the increase in intracellular Ca2+ but did not inhibit GTPM increase. These results indicate that chloroquine, via the Gβγ-PLC-IP3-IP3R pathway, induces elevation of Ca2+, and this Ca2+ increase does not play a role in chloroqui-ne-evoked GTPM increase. However, GLUT4 fusion with the PM and glucose uptake were significantly inhibited with BAPTA-AM. This suggests that Ca2+ enhances GLUT4 fusion with the PM resulting in glucose uptake increase. Conclusion: Our data indicate that chloroquine via Gβγ-PLC-IP3-IP3R induces Ca2+ elevation, which in turn promotes GLUT4 fusion with the PM. Moreover, chloroquine can enhance GLUT4 trafficking to the PM. These mechanisms eventually result in glucose uptake increase in control and insulin-resistant L6 cells. These findings suggest that chloroquine might be a potential drug for improving insulin tolerance in diabetic patients.